Effects of study abroad on the career: The case of graduates from a Japanese university (Comparative & International Education Series, 2021)
This study investigates factors to determine the participation into study abroad (SA) and the mechanism how experience of SA influences on the educational outputs (competencies) and outcomes (career) using survey data of graduates majored in social sciences at a Japanese university (N=1,271). The results of empirical analysis show followings; First, the factor to determine SA experience is clarified as students’ attributes and engagement in the study for a cognitive knowledge and a foreign language. Second, SA experience has relationship with educational outputs such as generic, field-specific, and international competencies. Finally, the career, shown as wage and recognition of leadership or innovative work, is based on college outputs derived from an educational engagement including SA.